The Accounting Accountability Supports Good Corporate Governance for Public Companies: - - Rochendi, Teddy; Soesanto, Slamet (Politeknik Negeri Jakarta, 2023)
Good Corporate Governance - GCG is an indication of the establishment of the business actors’s integrity, and the efficient use of company resources and meeting the expectations of stakeholders. As a GCG system, it regulates and controls the company in order to prevent misuse of resource and continue to encourage the company's growth to create added value for all parties. Public companies need good governance like other companies where the interests of the parties must be protected. The correlation between the application of GCG principles and accounting accountability is reflected in the internal control system in which accounting is a part. Accounting accountability is guaranteed if internal control practices are carried out properly as a form of GCG development in public companies. Keywords: Good Corporate Governance, Public Company